Synthesis of polysulfone/polyamide thin film nanocomposite membranes for forward osmosis applications - Rashed, Ahmed Omaia Abdelfattah Mohamed (AUC Knowledge Fountain, 2018)
Forward osmosis (FO) has attracted significant interest as a promising alternative to reverse osmosis (RO) in membrane-based water desalination applications. FO water flux, salt rejection and reverse solute flux are three critical parameters affecting membrane performance. Thin film composite (TFC) membranes have been widely used in FO processes. A typical TFC membrane consists of a rejection polyamide (PA) layer on top of a highly porous support layer. In the current study, carboxyl functionalized multi-walled carbon nanotubes (F-MWCNTs) were used as nano-fillers in the membrane rejection layer to enhance the FO membrane performance. Polyamide (PA) thin film nano-composite (TFNC) membranes were synthesized on top of polysulfone (PSF) porous support layers by interfacial polymerization (IP) using m-phenylenediamine (MPD) in water and trimesoyl chloride (TMC) in hexane. The PSF support layer was synthesized by phase inversion in a water bath of a casting solution of PSF and polvinylpyrrolidone (PVP) (pore forming agent) dissolved in anhydrous dimethyl formamide (DMF). Multi-walled carbon nanotubes were functionalized by oxidation in strong acidic solutions, and then incorporated in the MPD aqueous solution during IP. For the support layer, PSF and PVP concentrations were varied while monomers (MPD, TMC) concentrations, contact time and curing temperature were varied for the rejection layer. Experimental designs for both the support and the rejection layers were carried out using Design-Expert software including statistical analysis to identify the most significant factors affecting the membrane performance. The support layer of 18 wt% PSF and 2 wt% PVP was selected as the membrane support with the highest possible FO water flux and minimum reverse solute flux while the PA rejection layer of 4 wt/vol% MPD and 0.2 wt/vol% TMC was selected as the membrane rejection layer with a salt rejection of 88.30±0.11%. Finally, the amount of F-MWCNTs was varied from 0.01 to 0.2 wt/vol% to study their effect on the membrane morphology and performance. The synthesized membranes were characterized using Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Fourier Transform Infrared Spectrophotometry (FTIR) and Brunauer-Emmett-Teller gas adsoprtion analysis (BET). FO performance was investigated using deionized water as the feed solution and 2 M NaCl as the draw solution. It was found that F-MWCNTs enhanced the membrane hydrophilicity and surface roughness that led to increased FO water flux. Most importantly, the salt rejection was also increased at low concentrations of F-MWCNTs (< 0.05 wt/vol%). The membrane with 0.01 wt/vol% F-MWCNTs showed the highest salt rejection (90.05±0.25%) with a FO water flux of 50.23±0.93 L/m2 h and a reverse solute flux of 2.76±0.21 g/m2h, thus outperforming thin film composite FO membranes reported in literature.